Sacrifice and Tribute in Hosea 6:6: The Implication of Contextual Worshipping - Susila, Tirta (Interdisciplinary Social Studies, 2022)
Hosea was not the only prophet who saw and criticized the falsehood of the Israelites' worship as God's people. Hosea's specialty, however, is that in his preaching he repeatedly puts forward, and therefore, reflects a fairly detailed theological concept of understanding the true, meaningful, and proper worship of God's people. In his preaching, Hosea highlighted two things in connection with Israel's worship, namely between the "loyal love / hesed and knowing God / daat elohim" versus the "sacrifice" / zebakh and the burnt offering/ola. The words hesed and da?at 'elohim are words and terms (formulas) that reveal the essence of Hosea's theological understanding of the true worship of Yahweh, which God's people should embody so that their relationship with God is maintained. In this term, there is an understanding of the "fundamental principles," "the premises," "the fundamental character," the "basic ideas," of worshiping Yahweh.